6
$\begingroup$

I am learning this method for solving PDSs by means of power series. Since I am studying it with lecture notes and I can't find any other book that describes this method, I am going to summarize it below then I ask my question.

A general PDE can be written as: $$F(u,u_{yy},u_{xx},u_{xy},u_{x},u_{y},x,y)=0$$ where $u=u(x,y)$. So, if we able able to solve this equation for $u_{yy}$ we can write $$u_{yy}=f(u_{xx},u_{xy},u_{x},u_{y},x,y) $$ Then, we are given the following side conditions: $u(x,0)$ and $u_{y}(x,0)$, such that we are able to find the other derivatives at $(x,0)$. Then, we can use a power series around $y=0$ to find $u(x,y)$: $$u(x,y)=u(x,0)+yu_{y}(x,0)+\frac{y^2}{2!}u_{yy}(x,0)+\frac{y^3}{3!}u_{yyy}(x,0)+... $$

For example, suppose we have the PDE $u_{xx}-u_{yy}=0$ with the conditions $u(x,0)=x^2+x$ and $u_{y}(x,0)=2x+1$. It follows that $u_{x}(x,0)=2x+1$ and $u_{xx}(x,0)=2=u_{yy}(x,0)$ (this last equality is true because of the PDE). Then if we differentiate $u_{yy}(x,0)$ with respect to $y$ we get $u_{yyy}(x,0)=u_{yyyy}(x,0)=...=0$. Then, the solution as a power series is $$u(x,y)=x^2+x+y(2x+1)+y^2 $$ which satisfy the PDE and the side conditons.

Now, my question is about the following problem: $$u_{t}=u_{xx}$$ with the side conditions $u(0,t)=t^2$ and $u_{x}(0,t)=0$. In this case, I know the function along the t-axis, so I should try to apply this method by writing a power series around $x=0$. To do this, I need to find the derivatives of $u$ with respect to $x$. Since $u(0,t)=t^2$, we have $u_{t}(0,t)=2t$=$u_{xx}(0,t)$ (again, this is true because of the PDE). If I derive $u_{xx}(0,t)$ with respect to $x$, I can get higher derivatives to write the power series. But it turns out the $u_{xx}(0,t)=u_{xxx}(0,t)=...=0$ because $u_{xx}(0,t)$ only depends on $t$. Thus, we can write: $$u(x,t)=u(0,t)+xu_{x}(0,t)+\frac{x^2}{2!}u_{xx}(0,t)+\frac{x^3}{3!}u_{xxx}(0,t)+...=t^2+x^2t $$But this solution does not satisfy the PDE. What is wrong with this reasoning?

$\endgroup$
  • 1
    $\begingroup$ I used your example for demonstrating SymPy PDE solving over here. $\endgroup$ – Foad Aug 2 '18 at 11:54
  • 1
    $\begingroup$ @Foad very interesting. Thanks for bringing this up. $\endgroup$ – Thiago Oct 24 '18 at 21:21
4
$\begingroup$

The mistake is that $u_{xxxx}(0,t) \neq 0$. We have

$$\begin{align} u_{xxxx}(0,t) &= (u_{xx})_{xx}(0,t)\\ &= (u_t)_{xx}(0,t)\\ &= (u_{xx})_t(0,t)\\ &= u_{tt}(0,t)\\ &= 2. \end{align}$$

And therefore you get

$$u(x,t) = u(0,t) + \frac{x^2}{2}u_{xx}(0,t) + \frac{x^4}{4!}u_{xxxx}(0,t) = t^2 + tx^2 + \frac{1}{12}x^4,$$

which satisfies $u_t = u_{xx}$.

(Since $u_{ttt}(0,t) \equiv 0$, we need not convert higher derivatives wrt $x$ to derivatives wrt $t$.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.